1996
DOI: 10.1016/0014-5793(96)00253-0
|View full text |Cite
|
Sign up to set email alerts
|

Heparin protection against Fe2+‐and Cu2+‐mediated oxidation of liposomes

Abstract: Heparin (HE) exhibited a protective effect on liposome peroxidation induced by Fe 2+ and Cu 2+, decreasing the formation of both conjugated dienes and thiobarbituric acid reactive substances (TBARS) in a dose-dependent manner. The antioxidant activity was more relevant in the oxidizing system employing Fe 2+ and H202 and generating the highly reactive "OH radical. The analysis of liposome size distribution by quasielastic laser light scattering showed that: (1) the native structure of the particles was complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…These results are similar to those when heparin was added to Fe 2+ or Cu 2+ initiated peroxidation of liposomes formed from phosphatidylcholine [45]. The rate of Fe 2+ oxidation is extremely low in liposomal suspensions and is not affected by the absence or presence of heparin (Figure 2, panel a ).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…These results are similar to those when heparin was added to Fe 2+ or Cu 2+ initiated peroxidation of liposomes formed from phosphatidylcholine [45]. The rate of Fe 2+ oxidation is extremely low in liposomal suspensions and is not affected by the absence or presence of heparin (Figure 2, panel a ).…”
Section: Resultssupporting
confidence: 82%
“…The ability of heparin to inhibit the Fe 2+ initiated peroxidation of linolenic acid was first demonstrated by Ross et al [53]. Albertini, R. et al have shown that heparin inhibits Fe 2+ or Cu 2+ initiated peroxidation of phosphatidylcholine liposomes [45]. On the basis of liposome size and the presence or absence of heparin, the authors concluded that heparin interacts with phospholipids to make them less susceptible to lipid peroxidation [45].…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that the sulphated glycosaminoglycans actually bind ؒ OH-promoting iron and copper ions via their sulphate groups, thereby preventing these ions from enhancing ؒ OH production and glycosaminoglycan chain degradation (Grant et al, 1992a(Grant et al, , 1992bWilliamson et al, 1992). Indeed, numerous studies now recognise heparin and other sulphated glycosaminoglycans as potent antioxidants (Albertini et al, 1995(Albertini et al, , 1996a(Albertini et al, , 1996b(Albertini et al, , 1997Grant et al, 1996). The opposite is true for hyaluronan and heparin exposed to NO ؒ , with heparin being more susceptible to degradation than hyaluronan, since the amino groups of Nacetylglucosamine residues in hyaluronan are blocked by N-acetyl groups, rendering these regions resistant to NO ؒ breakdown.…”
Section: Ros Degradation Of Cartilage Proteoglycan and Glycosaminoglymentioning
confidence: 99%
“…Thioredoxin reductase, another enzyme thought protective in oxidative brain injury [ 130 , 131 ], also demonstrates high affinity binding to heparin [ 132 ], although the significance of this interaction is unclear. Several in vitro studies demonstrate direct antioxidant actions of the heparin molecule itself independent of any associated co-enzyme [ 133 , 134 ]. Taken together, these findings suggest that heparin may ameliorate the oxidative injury generated following aSAH.…”
Section: Heparin In Post-sah Brain Injurymentioning
confidence: 99%